Designing An Information System For Determining Product Shelf Layout At Indomaret In Suka Menanti Village Using Barcodes Data And The Apriori Methode - Defry, Geovano; Juhardi, Ujang; Rifqo, Muhammad Husni; Saputera, Surya Ade (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Determining the location of product displays is a crucial aspect of retail management because it affects customer comfort. Indomaret has a wide variety of products in many categories, so optimal display arrangement is a challenge in itself. Therefore, data-driven layout management is essential to optimize the shopping experience and increase sales. Advances in barcode technology and information systems enable real-time and accurate transaction data collection. Indomaret, as a widely distributed minimarket chain in Indonesia, plays a significant role in meeting the daily needs of the community, including in Suka Menanti Village. Data-driven shelf layout based on local transaction data will be more relevant and effective than a general approach, as purchasing patterns in rural areas may differ from those in urban areas. This study aims to design an information system that utilizes barcode transaction data and the Apriori method to determine product shelf layout, offering a suitable and innovative solution. This system will not only assist Indomaret in Suka Menanti Village in optimizing product layout but also enhance operational efficiency and the overall customer shopping experience.